2010
DOI: 10.1165/rcmb.2008-0132oc
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Attenuates Chronic Hypoxia–Induced Pulmonary Hypertension in a Mouse Model

Abstract: Chronic hypoxia contributes to pulmonary hypertension through complex mechanisms that include enhanced NADPH oxidase expression and reactive oxygen species (ROS) generation in the lung. Stimulation of peroxisome proliferator-activated receptor g (PPARg) reduces the expression and activity of NADPH oxidase. Therefore, we hypothesized that activating PPARg with rosiglitazone would attenuate chronic hypoxia-induced pulmonary hypertension, in part, through suppressing NADPH oxidase-derived ROS that stimulate proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
307
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(322 citation statements)
references
References 50 publications
14
307
1
Order By: Relevance
“…The therapeutic potential of PPARg agonists also reveals promise in animal models of PAH. In 2009, Nisbet and colleagues explored this pathway in the chronic hypoxic mouse PAH model (30). They found that treatment with rosiglitazone prevented the development of pulmonary hypertension at 3 weeks, reversed established pulmonary hypertension at 5 weeks, and from a mechanistic standpoint reduced NADPH oxidase (Nox4) expression, superoxide production, and platelet-derived growth factor (PDGF) receptor b activation.…”
Section: Peroxisome Proliferator-activated Receptor G and Pahmentioning
confidence: 99%
“…The therapeutic potential of PPARg agonists also reveals promise in animal models of PAH. In 2009, Nisbet and colleagues explored this pathway in the chronic hypoxic mouse PAH model (30). They found that treatment with rosiglitazone prevented the development of pulmonary hypertension at 3 weeks, reversed established pulmonary hypertension at 5 weeks, and from a mechanistic standpoint reduced NADPH oxidase (Nox4) expression, superoxide production, and platelet-derived growth factor (PDGF) receptor b activation.…”
Section: Peroxisome Proliferator-activated Receptor G and Pahmentioning
confidence: 99%
“…[28][29][30] The expression of PPARγ was reduced in lung tissue from PAH patients, rats with hypoxia-induced PAH, 31,32 as well as SMCs and endothelial cells isolated from mouse pulmonary arteries exposed to hypoxia. 33 Similarly, PAH developed in mice with SMC-or endothelial cellspecific deletion of PPARγ. 34,35 In contrast, PPARγ activation ameliorated PAH.…”
mentioning
confidence: 99%
“…34,35 In contrast, PPARγ activation ameliorated PAH. [32][33][34][36][37][38] However, the effect of PPARγ agonists on the vasoconstriction in PAH remains unknown.…”
mentioning
confidence: 99%
“…[322][323][324][325][326][327][328][329][330][331] PPAR␥ expression was decreased in several studies that used rodent models of PH, and PPAR␥ agonist treatment attenuated pulmonary vascular remodeling. [332][333][334][335] In an interesting recent study, Falcetti and colleagues demonstrated that PPAR␥ expression was enhanced in the medial layer of arteries from patients with idiopathic PH, compared to controls. 322 Whether that finding conflicts with the previous description of decreased lung tissue expression in advanced PH is unclear, since the initial study did not quantitate expression in the medial muscle layers.…”
Section: Statinsmentioning
confidence: 99%